Development of TCS3200 colour sensor based on Arduino Uno microcontroller for determination of capsaicin level in sauces - Khairi Suhud,; Dian Utari,; Muhammad Syukri Surbakti,; Sagir Alva,; Fairuz Omar,; Saiful Saiful,; Leny Heliawati,; Purnama Ningsih,; Andriy Anta Kacaribu,; Muhammad Daffa Hadistya,; Thariq Zaid Gunana,; Rinaldi Idroes, (Penerbit Universiti Kebangsaan Malaysia, 2024)
A colour sensor has been designed to measure the capsaicin level in commercial sauces. This system is designed using a TCS2300 colour sensor as an input, and an Arduino Uno microcontroller with Integrated Development Environment (IDE) software as signal conditioning and signal processing. The measurement result will be compared to the standard Ultraviolet-Visible (UV-Vis) spectrophotometer method. The sauce samples were taken using a sampling technique, namely eight samples of sauces circulating in the city of Banda Aceh. The result showed that the levels of capsaicin using the TCS3200 colour sensor and UV-Vis spectrophotometer ranged from 5.39 to 22.42 mg/L and 5.58 to 22.64 mg/L, respectively. The linearity obtained in the concentration range of 5.25 mg/L shows a linear calibration curve using the TCS3200 colour sensor (R2 = 0.9961) and UV-Vis Spectrophotometer (R2 = 0.9973). Accuracy (% recovery) for the TCS3200 colour sensor and UV-Vis spectrophotometer ranged from 98.94 to 106.63%, and 98.13 to 110.2% mg/L, respectively. In the case of interday and intraday relative standard deviation has not more than 2%. Based on the t-test assessment, it shows that the TCS3200 colour sensor has no differences statistically in results with UV-Vis Spectrophotometer. These results describe that the TCS3200 colour sensor can be an alternative for analyses of capsaicin in sauce samples.